A Study on Consumer Awareness towards Organic Products in Bangalore City - Hajira, Mrs. Bibi; Someswararao, Dr. K.V.V. Murali (The journal of contemporary issues in business and government, 2022)
Organic Products refers to the process of selling the products and services based on their interest and environmental benefits to the society. Organic Products is typically practiced by many environmental companies that are committed to environmental and social responsibility. Organic Products is a new strategy to protect society and environment. The main thrust of the study is to measure the relationship among consumer awareness and perception toward Organic Products. It is found that there is association between gender and annual income of consumers in Bangalore city and concluded that there is relationship between consumer awareness, consumer perception, environmental concerns, and consumer buying decision of Organic Products in Bangalore city.